Continental divergence in male reproductive plasticity to thermal and resource stress in a widespread dung fly - Lee, Nicole Li Ying; Tan, Jia Wei; Wang, Yi Bo; Tan, Tyrone Ren Hao; Puniamoorthy, Nalini (Frontiers in Ecology and Evolution, 2025)
IntroductionPhenotypic plasticity in critical life-history traits can buffer populations against environmental change, but its magnitude and direction may vary across geographic lineages.MethodsHere, we investigated how two major developmental stressors, rising temperatures and food limitation, affect life-history traits. We quantified variation in juvenile survival, development time, adult body size and male reproductive investment (testis size; sperm length) in Sepsis punctum (Fabricius, 1794), a widespread dung fly with different mating strategies and contrasting sexual size dimorphism (SSD) between North America (females larger) and Europe (males larger).Results and DiscussionElevated temperatures reduced larval survival and accelerated development, generating smaller adults, particularly in European populations, with no changes in SSD. Food limitation also reduced adult size but had little effect on juvenile survival. Instead, resource stress differentially impacted SSD; female-biased SSD persisted in North American populations, but male-biased SSD did not persist in European populations. Male reproductive investment showed partial resilience, where absolute trait sizes declined under both stressors, but size-independent investment remained largely stable. Testis size decreased with increasing temperature, while sperm length did not, suggesting potential canalization of sperm quality and a strategic resource allocation that trades off quantity under stress. We revealed continental divergence in phenotypic plasticity in S. punctum, highlighting the importance of geography and stressor type in shaping life-history trajectories. These findings indicate that thermal stress may have stronger evolutionary consequences than resource limitations, with implications for population resilience and reproduction under global change.